THE EFFECT OF LEARNING TIME MANAGEMENT, SELF-EFFICACY, LEARNING READINESS, PARENTAL SUPPORT, AND LEARNING INDEPENDENCE ON THE LEARNING ACHIEVEMENT OF GRADE XI STUDENTS IN PHASE F AT ECONOMICS SUBJECT AT SMA N 1 SITIUNG - Oknanta Saputra, Iqsan; Lovelly Dwinda Dahen; Fifi Yasmi (Global Action and Education for Society, 2026)
This study aims to analyze: 1) The effect of time management on academic achievement, 2) the effect of self-efficacy on academic achievement, 3) the effect of learning readiness on academic achievement, 4) the effect of parental support on academic achievement, 5) the effect of learning independence on academic achievement. The type of research used in this study is associative research.The research was conducted in July 2025. The population in this study was all 11th grade students in economics at SMAN 1 Sitiung. The sample in this study consisted of 107 people. The sampling technique used was random sampling, and the data analysis techniques used were descriptive analysis and inductive analysis, with the help of Eviews and SPSS version 21.0. The results of the study indicate that 1) time management affects learning achievement with a coefficient value of -0.208, a t-value of 2.126 > t-table value of 1.983, and a significance value of 0.036 < 0.05. 2) Self-efficacy influences academic achievement with a coefficient value of 0.433, a calculated t-value of 2.004 > the table t-value of 1.983, and a significance level of 0.048 < 0.05. 3) Learning readiness influences academic achievement with a coefficient value of -0.547, a calculated t-value of 2.319 > the table t-value of 1.983, and a significance level of 0.022 < 0.05. 4) Parental support influences academic achievement with a coefficient value of -0.192, a calculated t-value of 2.026 > the table t-value of 1.983, and a significance level of 0.045 < 0.05. 5) Learning independence influences academic achievement with a coefficient value of -2.894, a calculated t-value of 2.324 > the critical t-value of 1.983, and a significance level of 0.022 < 0.05. 6) Time management, self-efficacy, readiness to learn, parental support, and learning independence together (simultaneously) significantly influence academic achievement. The calculated F value is 4.780 > the table F value of 2.30 and the significance value is 0.001 < 0.05.